2021
DOI: 10.3390/biology10050435
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of the Perfect Dancer’s Ballet Foot. The Footprint, Stabilometric, Pedobarographic Parameters of Professional Ballet Dancers

Abstract: This work aims to assess footprint parameters in a group of professional ballet dancers and to determine the correlation between the aforementioned parameters and lateralization, stabilometric parameters, pedobarographic parameters and work environment conditions. A group subjected to tests consisted of 44 elite professional ballet dancers and the reference group was composed of 44 students. The test of balance and thrust under feet involved 30 s-long free standing with open eyes on a podographic platform. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Humans have numerous regulatory mechanisms responsible for keeping a vertical body posture, and irregularities in the functioning of these mechanisms often lead to locomotor disorders that can result in falls and injuries ( Błaszczyk et al, 2016 ; Gorwa et al, 2021 ; Hof et al, 2005 ). Understanding the causes of postural disorders and achieving proper diagnosis is therefore essential.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have numerous regulatory mechanisms responsible for keeping a vertical body posture, and irregularities in the functioning of these mechanisms often lead to locomotor disorders that can result in falls and injuries ( Błaszczyk et al, 2016 ; Gorwa et al, 2021 ; Hof et al, 2005 ). Understanding the causes of postural disorders and achieving proper diagnosis is therefore essential.…”
Section: Introductionmentioning
confidence: 99%
“…According to most authors investigating dancers’ feet, the muscles responsible for the foot and ankle joint should be able to sustain appropriately high force to perform pointé-work ( 26 , 27 ). The introduction of pointé-work-related exercises before the dancer’s feet obtain their functional maturity weakens the feet and increases their susceptibility to injuries ( 27 ). Plantar flexion of 180º in relation to the central axis of the tibial bone and foot is a pre-condition of proper, entire, and safe pointé-work ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of pointé-work-related exercises before the dancer’s feet obtain their functional maturity weakens the feet and increases their susceptibility to injuries ( 27 ). Plantar flexion of 180º in relation to the central axis of the tibial bone and foot is a pre-condition of proper, entire, and safe pointé-work ( 26 , 27 ). However, the combination of high impact loads, defined as the level of maxGRF z (5.31–11.11 BW for the analyzed jumps), and weakness caused by the premature introduction of pointé-work in technical exercises of classical dance increase injury risk and leads to a high percentage of metatarsus (80%) and ankle joint (83.3%) injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Stabilometry has been a commonly used method to assess the static balance of dancers in previous studies. 5,7,8 Measuring the center of pressure (COP) has been shown to be a reproducible assessment for static balance. 9 In previous studies, dancers showed a small COP displacement with single-leg support on the force platform, which suggested that they had better balance ability than non-dancers.…”
Section: Investigation Of the Relationship Between The Morphology Of ...mentioning
confidence: 99%